Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2025)
Quentin Skinner. 2025. Liberty as Independence: The Making and Unmaking of a Political Ideal. Cambridge: Cambridge University Press, 332 pp. Cédric M. Koch. 2025. “The People” vs. the Liberal International Order?: Varieties of Populism and the International Politics of Democratic Legitimacy. Nueva York: Oxford University Press, 778 pp. Wolfgang Streeck. 2024. Taking Back Control?: States and State Systems after Globalism. Traducción al inglés de Ben Fowkes y Joshua Rahtz. Londres: Verso. Paula Diehl y Michael Saward. 2025. Bodies, Spaces, Claims: The Theory and Practice of Performing Political Representation. Nueva York: Oxford University Press, 480 pp. Tom Ginsburg, Aziz Z. Huq y Tarun Khaitan, eds. 2024. The Entrenchment of Democracy: The Comparative Constitutional Design of Elections, Parties and Voting. Comparative Constitutional Law and Policy. Cambridge: Cambridge University Press. Martha Singer Sochet y Rosa Merlín Rodríguez, coords. 2024. Temas selectos contemporáneos de Estado, Sociedad y Derecho. Ciudad de México: Facultad de Ciencias Políticas y Sociales, Universidad Nacional Autónoma de México, 320 pp.. Scott Williamson. 2024. The King Can Do No Wrong: Blame Games and Power Sharing in Authoritarian Regimes. Cambridge: Cambridge University Press, 350 pp. Patricia Owens. 2025. Erased: A History of International Thought without Men. Princeton: Princeton University Press, 432 pp. Alec Stone Sweet y Wayne Sandholtz. 2024. The Law and Politics of International Human Rights Courts: The Dilemma of Effectiveness. Nueva York: Oxford University Press, 304 pp.